2021
DOI: 10.3324/haematol.2021.278334
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnostic value of telomere length measurement in inherited bone marrow failure syndromes

Abstract: Not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
1
2
0
3
Order By: Relevance
“…37 Further, the diagnostic value of TL in 133 patients with BMF was evaluated and compared in patients with DKC, non-DKC IBMFS, and AA. This study observed no significant difference in telomere length between non-DC IBMFS (FA: 9/15) compared to AA, 38 aligning with our data. This may be due to the lower age group…”
Section: Discussionsupporting
confidence: 91%
“…37 Further, the diagnostic value of TL in 133 patients with BMF was evaluated and compared in patients with DKC, non-DKC IBMFS, and AA. This study observed no significant difference in telomere length between non-DC IBMFS (FA: 9/15) compared to AA, 38 aligning with our data. This may be due to the lower age group…”
Section: Discussionsupporting
confidence: 91%
“…В опубликованных исследованиях уже отмечалось, что ДТ в общей группе больных АА может быть сопо ставима с ДТ у здоровых доноров [6,8]. В нашей рабо те мы показали, что нет статистически значимых раз личий ДТ в мононуклеарах периферической крови и костного мозга больных АА и здоровых доноров.…”
Section: Discussionunclassified
“…Отдельного внимания заслуживают исследования по изучению длины теломер (ДТ), укорочение которых можно обнаружить у 5-25 % больных АА [6][7][8]. При этом в общей группе больных ДТ обычно соответству ет здоровому контролю, в отличие от ВД -конститу циональной АА, в патогенезе которой ведущую роль играют соматические мутации в генах теломеразного комплекса, ответственного за восстановление утрачен ных в ходе клеточного деления терминальных гексапо второв TTAGGG теломерных районов ДНК.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…We recently performed a retrospective analysis of 133 patients with BMF, including 107 with AA and 26 with IBMFSs, who were genetically diagnosed by next-generation sequencing. 3 To achieve definitive diagnosis, a combination of clinical information, laboratory results, and genetic testing was used. In 112 of these patients, PNH-type granulocytes and red blood cells were also evaluated by flow cytometry.…”
mentioning
confidence: 99%